Eksistensi Partai Politik Lokal di Provinsi Papua Pasca Putusan Mahkamah Konstitusi Nomor 41/PUU-XVII/2019 - Galih Raka Siwi; Reviansyah Erlianto; Maharani Nurdin (ADLIYA: Jurnal Hukum dan Kemanusiaan, 2021)
The existence of local political parties in Indonesia is a tangible form of the existence of special autonomy in a certain area. The specificity of a certain area is regulated in the 1945 Constitution Article 18B paragraph (1). In addition, the formation of local political parties is one of the human rights in the political field, as stated in Article 28E paragraph (3) of the 1945 Constitution. The research method uses a normative juridical approach with secondary data and analyzed descriptively qualitatively. Based on research, Papua Province has the right to form political parties (see Article 28 paragraph (1) of the Papua Province Special Autonomy Law). However, the phrase "political party" is considered to have multiple interpretations, thus creating legal uncertainty. Through the decision of the Constitutional Court Number 41/PUU-XVII/2019, the legal uncertainty can be guaranteed by the Constitutional Court Decision. In the future, by looking at the background and real needs of the Papua Province, it is possible to form a Local Political Party in the Papua Province, considering the condition of the Papua Province as a special autonomous region.Partai politik lokal di Indonesia merupakan wujud nyata adanya otonomi khusus di suatu daerah. Kekhususan suatu daerah diatur dalam UUD 1945 Pasal 18B ayat (1). Selain itu, pembentukan partai politik lokal merupakan salah satu hak asasi manusia di bidang politik, sebagaimana tercantum dalam Pasal 28E ayat (3) UUD 1945. Metode penelitian menggunakan pendekatan yuridis normatif dengan data sekunder dan dianalisis secara deskriptif kualitatif. Berdasarkan penelitian, Provinsi Papua berhak membentuk partai politik (lihat Pasal 28 ayat (1) UU Otsus Provinsi Papua). Namun, ungkapan “partai politik” dianggap memiliki multitafsir sehingga menimbulkan ketidakpastian hukum. Melalui putusan MK Nomor 41/PUU-XVII/2019, ketidakpastian hukum dapat dijamin oleh Putusan MK tersebut. Ke depan, dengan melihat latar belakang dan kebutuhan riil Provinsi Papua, dimungkinkan dibentuknya Partai Politik Lokal di Provinsi Papua, mengingat kondisi Provinsi Papua sebagai daerah otonomi khusus.